Topological Characterization of Human and Mouse m5C Epitranscriptome Revealed by Bisulfite Sequencing - Zhen Wei; Subbarayalu Panneerdoss; Santosh Timilsina; Jingting Zhu; Tabrez A. Mohammad; Zhi-Liang Lu; João Pedro de Magalhães; Yidong Chen; Rong Rong; Yufei Huang; Manjeet K. Rao; Jia Meng (International Journal of Genomics)
Background. Compared with the well-studied 5-methylcytosine (m5C) in DNA, the role and topology of epitranscriptome m5C remain insufficiently characterized. Results. Through analyzing transcriptome-wide m5C distribution in human and mouse, we show that the m5C modification is significantly enriched at 5′ untranslated regions (5′UTRs) of mRNA in human and mouse. With a comparative analysis of the mRNA and DNA methylome, we demonstrate that, like DNA methylation, transcriptome m5C methylation exhibits a strong clustering effect. Surprisingly, an inverse correlation between mRNA and DNA m5C methylation is observed at CpG sites. Further analysis reveals that RNA m5C methylation level is positively correlated with both RNA expression and RNA half-life. We also observed that the methylation level of mitochondrial RNAs is significantly higher than RNAs transcribed from the nuclear genome. Conclusions. This study provides an in-depth topological characterization of transcriptome-wide m5C modification by associating RNA m5C methylation patterns with transcriptional expression, DNA methylations, RNA stabilities, and mitochondrial genome.